SISTEM INFORMASI ADMINISTRASI KEUANGAN SEKOLAH BERBASIS WEB (STUDI KASUS: SMK AL-KAHFI) (Jurnal Informatika Teknologi dan Sains, 2020)
Al-Kahfi Vocational School is a place where writers conduct research. At this time, the school's financial administration management system is still done manually, causing a lot of bookkeeping, repeated writing of data, and delays in making reports. The solution to the problem that is happening at Al-Kahf Vocational School is the application of information technology, namely building an information system that can help manage the school's financial administration system more efficiently. So from that the purpose of this study is the creation of a Web-Based School Financial Administration Information System at Al-Kahf Vocational School. This system was developed using the PHP programming language Hypertext Preprocessor (PHP) and MySql as a database. The existence of an information system built is expected to be able to help financial officers in the processing of school financial administration data so as to produce a well-organized school financial administration information system.